MIMO techniques and applications - Silva, Mário Marques da (2017)
First generation of cellular networks (1G) were analogue, having been deployed between 1980 and 1992. 1G included a myriad of cellular systems, namely the total access communication system (TACS), the advanced mobile phone system (AMPS), the Nordic mobile telephony (NMT), among others. These systems were of low reliability, low capacity, low performance, and without roaming capability between different networks and countries. The multiple access technique adopted was frequency division multiple access (FDMA), where signals of different users are transmitted in different (orthogonal) frequency bands. The second generation of cellular networks (2G), like the global system for mobile communications (GSM), was widely used between 1992 and 2003. This introduced the digital technology in the cellular environment, with a much better performance, better reliability, higher capacity, and even with the roaming capability between operators, due to its high level of standardization and technological advancements. The multiple access technique used by GSM was time division multiple access (TDMA), where signals generated by different users were transmitted in different (orthogonal) time slots. Narrowband code division multiple access (CDMA) system was adopted in the nineties by IS-95 standard, in the United States. IS-95 was also a 2G system. Afterwards, the Universal Mobile Telecommunications System (UMTS), standardized in 1999 by the Third Generation Partnership Project (3GPP) release 99 (see Table 1.1), proceeded with its utilization, in this particular case using the Wideband CDMA (WCDMA). The UMTS consists of a third generation cellular system (3G). The CDMA concept relies on different spread spectrum transmissions, each one associated to a different user’s transmission, using a different (ideally orthogonal) spreading sequence. The long term evolution (LTE) can be viewed as the natural evolution of 3G , using a completely new air interface, as specified by 3GPP release 8, and enhanced in its release 9. Its initial deployment took place in 2010. The LTE comprises an air interface based on orthogonal frequency division multiple access (OFDMA) in the downlink and single carrier - frequency division multiple access (SC-FDMA) in the uplink. This allows a spectral efficiency improvement by a factor of 2 to 4, as compared to the high speed packet access (HSPA), making use of new spectrum, different transmission bandwidths from 1.4 MHz up to 20 MHz, alongside with multiple input multiple output (MIMO) systems and the all-over IP architecture.